2019
DOI: 10.1038/s41420-019-0168-4
|View full text |Cite
|
Sign up to set email alerts
|

Sirt6-induced autophagy restricted TREM-1-mediated pyroptosis in ox-LDL-treated endothelial cells: relevance to prognostication of patients with acute myocardial infarction

Abstract: Inflammation mediated by myeloid cells trigger receptors 1 (TREM-1) is important for atherosclerosis development, while sirtuin 6 (Sirt6) levels decrease in atheroscleoritc plaque. Here we demonstrate that oxidatively modified low density lipoprotein (ox-LDL)-treated endothelial cells (ECs) exhibited increased TREM-1-mediated pyroptosis and decreased Sirt6-induced autophagy. We show that high sTREM-1 and low sSirt6 levels were independent predictors of boosted endothelial microparticles (EMPs) on admission, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…Conversely, TREM1 inhibition alleviates ER stress and rescues the autophagy pathway, which ameliorates gut dysbiosis and reduces colitis severity. In addition, oxidatively modified low-density lipoprotein (ox-LDL)-treated endothelial cells (ECs) exhibit increased TREM-1-mediated pyroptosis and decreased Sirt6-induced autophagy [103]. Conversely, blockage of Sirt6-induced autophagy augments TREM-1-mediated pyroptosis, whereas Sirt6 overexpression attenuates ECs inflammation and pyroptosis following ox-LDL treatment.…”
Section: Autophagy As An Emerging Pathway Related To Trems Pathophmentioning
confidence: 99%
“…Conversely, TREM1 inhibition alleviates ER stress and rescues the autophagy pathway, which ameliorates gut dysbiosis and reduces colitis severity. In addition, oxidatively modified low-density lipoprotein (ox-LDL)-treated endothelial cells (ECs) exhibit increased TREM-1-mediated pyroptosis and decreased Sirt6-induced autophagy [103]. Conversely, blockage of Sirt6-induced autophagy augments TREM-1-mediated pyroptosis, whereas Sirt6 overexpression attenuates ECs inflammation and pyroptosis following ox-LDL treatment.…”
Section: Autophagy As An Emerging Pathway Related To Trems Pathophmentioning
confidence: 99%
“…Sirtuins (SIRT1-SIRT7) are evolutionary conserved nicotinamide adenine dinucleotide (NAD + )-dependent class III histone deacetylases which have attracted much attention for their roles in cardiovascular and metabolic diseases. 24 As an important member of sirtuin family, SIRT6 is mainly located in the nucleus and its activation exerts protective effects against myocardial infarction, 25 cardiac hypertrophy, 26 and heart failure. 27 Besides, numerous studies have reported that sirtuins mediated the pleiotropic actions of melatonin in various disease models.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence indicates that autophagic flux becomes defective in macrophages of advanced atherosclerotic plaques, and that treatment with an autophagy inducer can be exploited as a potential strategy to prevent plaque formation and destabilization ( 8 ). In endothelial cells cultured in vitro oxLDL-induced pyroptosis is restricted by autophagy ( 29 ). Consequently, we speculated whether, in our foam macrophages, pyroptosis can be counterbalanced by induction of autophagy.…”
Section: Resultsmentioning
confidence: 99%